Human Bone Marrow-Resident Natural Killer Cells Have a Unique Transcriptional Profile and Resemble Resident Memory CD8+ T Cells - Melsen, Janine E.; Lugthart, Gertjan; Vervat, Carly; Kielbasa, Szymon M.; van der Zeeuw, Sander A. J.; Buermans, Henk P. J.; van Ostaijen-ten Dam, Monique M.; Lankester, Arjan C.; Schilham, Marco W. (Frontiers in Immunology, 2018)
Human lymphoid tissues harbor, in addition to CD56bright and CD56dim natural killer (NK) cells, a third NK cell population: CD69+CXCR6+ lymphoid tissue (lt)NK cells. The function and development of ltNK cells remain poorly understood. In this study we performed RNA sequencing on the three NK cell populations derived from bone marrow and blood. In ltNK cells, 1353 genes were differentially expressed compared to circulating NK cells. Several molecules involved in migration were downregulated in ltNK cells: S1PR1, SELPLG and CD62L. By flow cytometry we confirmed that the expression profile of adhesion molecules (CD49e-, CD29low, CD81high, CD62L-, CD11c-) and transcription factors (Eomeshigh, Tbetlow) of ltNK cells differed from their circulating counterparts. LtNK cells were characterized by enhanced expression of inhibitory receptors TIGIT and CD96 and low expression of DNAM1 and cytolytic molecules (GZMB, GZMH, GNLY). Their proliferative capacity was reduced compared to the circulating NK cells. By performing gene set enrichment analysis we identified DUSP6 and EGR2 as potential regulators of the ltNK cell transcriptome. Remarkably, comparison of the ltNK cell transcriptome to the published human spleen-resident memory CD8+ T (Trm) cell transcriptome revealed an overlapping gene signature. Moreover, the phenotypic profile of ltNK cells resembled that of CD8+ Trm cells in bone marrow. Together, we provide transcriptional and phenotypic data that clearly distinguish ltNK cells from both the CD56bright and CD56dim NK cells and substantiate the view that ltNK cells are tissue-resident cells which are functionally restrained in killing and have low proliferative activity.